Genetic evidence for the association between COVID-19 epidemic severity and timing of non-pharmaceutical interventions - Manon Ragonnet-Cronin; Olivia Boyd; Lily Geidelberg; David Jorgensen; Fabricia F. Nascimento; Igor Siveroni; Robert A. Johnson; Marc Baguelin; Zulma M. Cucunubá; Elita Jauneikaite; Swapnil Mishra; Oliver J. Watson; et al. (Nature Communications, 2021)
Estimating the effects of non-pharmaceutical interventions for COVID-19 is challenging, partly due to variations in testing. Here, the authors use viral sequence data as an alternative means of inferring intervention effects, and show that delays in implementation resulted in more severe epidemics.